Love, satisfaction and exhaustion in the nursery: methodological issues in evaluating the impact of Work Discussion groups in the nursery. Issue 7 (3rd July 2018) - Elfer, Peter; Greenfield, Sue; Robson, Sue; Wilson, Dilys; Zachariou, Antonia
ABSTRACT: The significance of practitioners' emotions in nursery interactions is evident in vivid accounts from widely different socio-cultural contexts. Work Discussion (WD) is a model of professional reflection distinctive in its attention to emotion in work interactions. Psychoanalytic conceptions, particularly the notion of the defended subject, underpin WD. Enabling participants in WD to discuss subjective work experience in an open way is thus subtle and sensitive. Research has not addressed how the impact of different models of professional reflection may be evaluated. Can WD, with its explicit attention to the emotions evoked at work, strengthen practitioners' engagement with children and families? This paper critically discusses the complex methodological issues in evaluating the impact of WD on nursery practitioners, children and parents in the nursery. The challenge is to combine the intense subjectivity of WD with an evaluation that is rigorous and objective. Later papers will illustrate data analysis and report findings.